Encountering Art: Illuminating the invisible student and Language and Learning Adviser experience - Fraser, Terrie; Wright-Neville, Caroline; Grossi, Vittoria; Bak, Tao (Journal of Academic Language and Learning, 2023)
The role and professional identity of a Language and Learning Adviser (LLA) are often misunderstood within the university, especially within faculties, by academics and management. This paper reports on a multimodal project which sought to provide an avenue for expression of LLAs’ frustration with this lack of recognition using art practice-led research (PLR) methodology. Although the LLA experience has been examined by the profession from numerous positions, there has not been a study using PLR methods that captures the subjective experience of LLAs’ work experience and their perceptions of the student and LLA encounter. By employing PLR in a workplace where participants had not been trained as artists, unique visual and textual insights about individual LLAs’ perceptions of these encounters were generated. Artworks were created which are material evidence, or mediating objects that represent new understandings, augment new ways to be visible and, through participant discussion and analysis, provide new opportunities to voice professional quandaries, values and possibilities. The aim was to make visible the constraints and possibilities under which LLAs work, so those outside the profession might come to a deeper understanding of the LLA role, including how LLAs can collaborate with academics to develop academic skills within curriculum design. This paper and visual artefact is a record and expression of the ways LLAs face the issue of invisibility in their practice and how an art project brought the group together in meaningful and affirming ways.